On the 80th Birthday of Dmitry Borisovich Fuchs - Fialowski, Alice; Fuchs, Ekaterina; Fuchs, Elena; Khesin, Boris; Kirillov, Alexandre; Malikov, Fedor; Ovsienko, Valentin; Sossinsky, Alexei; Tabachnikov, Serge (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
This article is a collection of several memories for a special issue of SIGMA devoted to Dmitry Borisovich Fuchs.